Komparasi Regulasi Tentang Perseroan Terbatas Perseorangan Bagi Usaha Mikro Dan Kecil Negara Indonesia Dan United Kingdom - Bonita, Mutia Ria (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2023)
Limited Liability Company, hereinafter referred to as the Company based on Law no. 6 of 2023 is a a legal entity which is a capital partnership, established based upon an agreement, carrying out business activities with an authorized capital wholly divided into shares or Individual Legal Entities that meet the criteria of Micro and Small Scale Businesses as regulated under laws and regulations on Micro and Small Scale Businesses. This research was carried out using a normative juridical approach that is descriptive in nature starting from the regulation regarding single member companies, establishments, and organs contained in single member company in Indonesia and the comparisons with the United Kingdom. The purpose of this paper is to make a comparison of the regulations governing single member companies in Indonesia and the United Kingdom.Keywords: single member companies; micro and small scale businesses; comparison.